Penile Reconstruction with Radial Forearm Free Flap—Present State of the Art - Jain, Vasundhra; S., Shravan Rai K.; G., Srilekha Reddy; Guin, Devajyoti; Gupta, Shikha; Murarka, Anil; Sharma, Mohit (Indian Journal of Plastic Surgery, 2024)
Background Patients with congenital or acquired penile defects face significant psychological trauma. Various methods for penile reconstruction have been described of which the free radial artery forearm flap using the tube-within-tube design is found to be the most commonly used. We have assimilated the best practices described at different times in our bid to standardize the technique and have strived to make it reproducible. The reconstructed phalluses with this method can withstand the test of time, allowing the patients to lead a normal life.Materials and Methods We conducted a retrospective review of the past 16 years and collected data for all radial forearm free flap phalloplasties. We have modified the design originally described by Biemer. The urethra is kept 1 cm longer than the shaft and the proximal 5 mm of the prospective urethra is not sutured to allow for spatulation of the urethral anastomosis.Results A total of nine patients were included out of which six patients had congenital malformations, two had traumatic injuries, and one had penile carcinoma. Six out of the nine patients had implants placed which were wrapped in fascia lata graft. One of these patients experienced displacement of the implant which needed to be repositioned. Three patients faced postoperative complications. All patients had tactile and erogenous sensation at the tip of the glans at the end of 1 year and all patients could micturate while standing. One patient's esthetic and functional outcome was compromised. One of the married patients has fathered a child through normal sexual intercourse.Conclusion Radial forearm phalloplasty done by this technique allows us to achieve consistently stable functional and esthetic outcomes. We firmly believe that this standardized protocol for penile reconstruction could be of great benefit to patients as well as to the treating reconstructive surgeon in their quest to achieve a completely rehabilitated patient.
Keywords: phalloplasty; penile reconstruction; penile implant